1999
DOI: 10.1007/s007750050380
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray crystallographic study of the binding sites of the azide inhibitor and organic substrates to ceruloplasmin, a multi-copper oxidase in the plasma

Abstract: Ceruloplasmin is a multi-copper oxidase, which contains most of the copper present in the plasma. It is an acute-phase reactant that exhibits a two- to three-fold increase over the normal concentration of 300 microg/ml in adult plasma. However, the precise physiological role(s) of ceruloplasmin has been the subject of intensive debate and it is likely that the enzyme has a multi-functional role, including iron oxidase activity and the oxidation of biogenic amines. The three-dimensional X-ray structure of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
1
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 1 publication
3
116
1
3
Order By: Relevance
“…This in fact provided the first evidence for the presence of the trinuclear Cu clusters in biology, which was confirmed by the first crystal structure of an MCO, ascorbate oxidase (AO) (16). However, crystal structures of azide-bound AO (17), ceruloplasmin (Cp) (18), and CotA (19) later showed disagreement with spectroscopy (the three are also different from one another), indicating that the azide binding only occurs at the T3 site.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…This in fact provided the first evidence for the presence of the trinuclear Cu clusters in biology, which was confirmed by the first crystal structure of an MCO, ascorbate oxidase (AO) (16). However, crystal structures of azide-bound AO (17), ceruloplasmin (Cp) (18), and CotA (19) later showed disagreement with spectroscopy (the three are also different from one another), indicating that the azide binding only occurs at the T3 site.…”
mentioning
confidence: 79%
“…Recent model studies combined with calculations have further demonstrated that the three Cu(II) centers in the trinuclear site are all bridged by a 3 -oxo ligand (8,9). In the absence of reducing substrate, NI slowly decays to the resting enzyme, in which the one remaining O atom of the O 2 is terminally bound as OH Ϫ to the T2 site, as indicated by 18 O isotope ratio MS (IRMS) (10,11) and 17 O EPR (12) experiments. Thus, this process requires the 3 -oxo-bridged NI to undergo a large rearrangement.…”
mentioning
confidence: 99%
“…The structure of apo human ceruloplasmin (hCP) (Zaitsev et al, 1999), containing 1046 residues, was taken as a template in simulation No 18. The apo-hCP contains three domains linked by¯exible loops freely moving in solution (Vachette, 1999).…”
Section: Aligning Multidomain Modelsmentioning
confidence: 99%
“…SD21 was investigated (Table 3). Sodium azide and sodium cyanide are known to inhibit MCOs and quinoproteins (Solomon et al 1996;Zaitsev et al 1999), and high concentrations of these inhibitors did inhibit Mn(II) oxidation. Surprisingly, o-phenanthroline, a specific copper chelator and known inhibitor of Mn(II) oxidation in other species, only partially inhibited Mn(II) oxidation at high concentrations-much higher than was required to inhibit Mn(II) oxidation in partially purified preparations of Pseudomonas putida GB-1 (Okazaki et al 1997).…”
Section: Multicopper Oxidase and Quinone Inhibitors Affect Mn Oxidationmentioning
confidence: 99%